Sellar and Suprasellar Tuberculoma - Banga, Manpreet Singh; Roy, Kaushik; V., Sandeep B.; Dasgupta, Sibaji (Indian Journal of Neurosurgery, 2018)
Tuberculosis is responsible for 20% of the intracranial space-occupying lesions in India, and tuberculomas of the sellar and suprasellar region comprise only 1% of all intracranial tuberculomas. The clinical and radiological features of these lesions mimic a typical pituitary adenoma. Surgery is not usually indicated, except for obtaining biopsies to confirm diagnosis, as these lesions tend to resolve with appropriate antitubercular therapy. There is no consensus regarding the type of antitubercular regimen and duration of the treatment as the experience with tuberculomas of pituitary is limited. We report a rare case of hypophyseal tuberculosis in a patient as a sequela of tuberculous meningitis, which is a rare complication of tubercular meningitis.
Keywords: pituitary; tuberculosis; antitubercular therapy